2013
DOI: 10.1037/a0033777
|View full text |Cite
|
Sign up to set email alerts
|

Mate preferences do predict attraction and choices in the early stages of mate selection.

Abstract: Although mate preference research has firmly established that men value physical attractiveness more than women do and women value social status more than men do, recent speed-dating studies have indicated mixed evidence (at best) for whether people's sex-differentiated mate preferences predict actual mate choices. According to an evolutionary, mate preference priority model (Li, Bailey, Kenrick, & Linsenmeier, 2002; Li & Kenrick, 2006; Li, Valentine, & Patel, 2011), the sexes are largely similar in what they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
211
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(228 citation statements)
references
References 71 publications
10
211
2
Order By: Relevance
“…The reason for this is that it depends on the predicted length of the future relationship with the potential partner. For short-term relationships, men and women care equally about physical attractiveness; whereas, for long-term relationships, it seems that women then care more about the man's social status (Li et al, 2013). Similarly, the importance of adhering to traditional gender role norms could be affected by expectations for the length of the relationships, as noted above.…”
Section: Limitations and Future Directionsmentioning
confidence: 97%
See 1 more Smart Citation
“…The reason for this is that it depends on the predicted length of the future relationship with the potential partner. For short-term relationships, men and women care equally about physical attractiveness; whereas, for long-term relationships, it seems that women then care more about the man's social status (Li et al, 2013). Similarly, the importance of adhering to traditional gender role norms could be affected by expectations for the length of the relationships, as noted above.…”
Section: Limitations and Future Directionsmentioning
confidence: 97%
“…However, Luo and Zhang (2009) point out that in face-to-face dating situations, men and women do not differ in how physical attractiveness affects their choices. Others have concluded that men generally choose partners based on physical attractiveness, and women choose partners primarily based on social status, but only when considering a long term relationship (Li, Yong, Tov, Sng, Fletcher, Valentine & Balliet, 2013). When looking for short-term relationships, physical attractiveness is found to be most important for both sexes (Li et al, 2013).…”
Section: Physical Attractivenessmentioning
confidence: 98%
“…Additionally, Eastwick, Finkel, and Eagly [10] found, in a laboratory setting, that participants were more attracted to a study confederate when his/her written profile was created to more closely match their own ideal partner preferences, but this link disappeared following an actual interaction between participants and the confederate. Eastwick and Finkel [9] have therefore suggested that individuals lack introspective awareness of what influences their actual mate choices (but see [21] and [14] for data suggesting that similarity between individuals' preferences and the qualities of interaction partners do predict actual choices using similar "get acquainted" paradigms).…”
Section: Initial Evidence That Individuals Form New Relationships Witmentioning
confidence: 99%
“…In this study, the masculine norm Playboy, which endorses sexual activities with casual partners (Parent & Moradi, 2010) was only related to DL. This aspect of body image may be perceived to be more physically attractive and advantageous when competing for short-term relationships (Lanzieri & Cook, 2013;Li et al, 2013).…”
Section: Drive For Leannessmentioning
confidence: 99%